Locoregional Therapy With Curative Intent Versus Primary Liver Transplant for Hepatocellular Carcinoma: Systematic Review and Meta-Analysis. Issue 8 (August 2017) - Murali, Arvind R.; Patil, Sanjeev; Phillips, Kirk T.; Voigt, Michael D.
Abstract : Background: Locoregional therapy with curative intent (CLRT) followed by salvage liver transplantation (SLT) in case of hepatocellular carcinoma (HCC) recurrence is an alternative to primary liver transplantation (LT) in selected patients with HCC. Methods: We performed a systematic review and meta-analysis of studies comparing the survival of patients treated with CLRT versus LT, stratified by the stage of liver disease, extent of cancer, and whether SLT was offered or not. Results: We included 48 studies involving 9835 patients (5736 patients with CLRT and 4119 patients with primary LT). Five-year overall survival (OS) and disease-free survival (DFS) was worse for all categories of CLRT combined, than for primary LT (odds ratio [OR] for OS, 0.59; 95% confidence interval [CI], 0.48-0.71; P < 0.01). However, 5-year OS for CLRT and primary LT was not significantly different among patients with (i) Child-A cirrhosis and (ii) single HCC lesion, although DFS was worse. When SLT was offered after CLRT, intention-to-treat analysis showed no significant difference in 5-year OS (OR, 1.0; 95% CI, 0.6-1.7) between CLRT-SLT and primary LT, though noninferiority could not be shown. Only 32.5% patients with HCC recurrence after CLRT actually received SLT, as the rest were not medically eligible. Thus, the DFS was worse with CLRT-SLT (OR, 0.31; 95% CI, 0.2-0.6) compared with LT. Conclusions: CLRT-SLT may be offered as first-line therapy to patients with HCC and well-compensated cirrhosis instead of primary LT because it may lead to better utilization of donor liver. However, a large proportion of patients with HCC recurrence after CLRT may not be candidates for SLT. Abstract : The decision to offer primary liver transplantation to attempted curative treatment of hepatocellular carcinoma remains uncertain. The authors conducted a meta-analysis and suggest that primary attempts at cure with local therapy results in higher survival and spare organs for transplantation.